2006
DOI: 10.1002/chin.200638041
|View full text |Cite
|
Sign up to set email alerts
|

Synthesis of Novel Thiazole and Pyrrolothiadiazine Derivatives from Aldehyde Thiosemicarbazones.

Abstract: Ring closure reactions O 0130 Synthesis of Novel Thiazole and Pyrrolothiadiazine Derivatives from Aldehyde Thiosemicarbazones. -Substituted thiosemicabazones (I) react with tetracyanoethylene (II) to form heterocyclic compounds of type (III)-(V). A plausible mechanism for the formation of the products is given. -(GOMAA, M. A.-M.; HASSAN*, A. A.; SHEHATTA, H. S.; Heteroat. Chem. 17 (2006) 4, 261-266; Dep. Chem., Fac. Sci., El-Minia Univ., El-Minia 61519, Egypt; Eng.) -M. Bohle 38-041

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1

Citation Types

0
3
0

Year Published

2008
2008
2023
2023

Publication Types

Select...
2

Relationship

1
1

Authors

Journals

citations
Cited by 2 publications
(3 citation statements)
references
References 1 publication
0
3
0
Order By: Relevance
“…The relationship between the ability of thiosemicarbazone to inhibit oxidation and the coplanarity of several conjugated fragments of the molecule is known; in addition, in the case of thiosemicarbazones with a phenolic substituent, the ability to intercept radicals is influenced by the possibility of forming a hydrogen bond between the phenolic OH and the azomethine group. To investigate the influence of these factors on the antioxidant properties of the substances, a conformational analysis can be performed [32][33][34].…”
Section: Introductionmentioning
confidence: 99%
“…The relationship between the ability of thiosemicarbazone to inhibit oxidation and the coplanarity of several conjugated fragments of the molecule is known; in addition, in the case of thiosemicarbazones with a phenolic substituent, the ability to intercept radicals is influenced by the possibility of forming a hydrogen bond between the phenolic OH and the azomethine group. To investigate the influence of these factors on the antioxidant properties of the substances, a conformational analysis can be performed [32][33][34].…”
Section: Introductionmentioning
confidence: 99%
“…4 Recently we reported that the reaction of various aldehyde 4phenylthiosemicarbazones la-d,g with ethenetetracarbonitrile (TCNE, 2) effected the formation of the heterocyclic systems 3-5 (Scheme 1). 5 Thus, products originating from both incorporation ofTCNE fragments (3,4) and of plain oxidative cyclisation (5) were found. 5 Ph-NH-~-NH-N=CH-Ar + S 1a-d,g esters with primary thioamides,7 and methyl phenylpropiolate and l-acylthiosemicarbazides give triazolothiazinones.…”
mentioning
confidence: 98%
“…5 Thus, products originating from both incorporation ofTCNE fragments (3,4) and of plain oxidative cyclisation (5) were found. 5 Ph-NH-~-NH-N=CH-Ar + S 1a-d,g esters with primary thioamides,7 and methyl phenylpropiolate and l-acylthiosemicarbazides give triazolothiazinones. 8 Less attention so far have received the reactions of thiosemicarbazones with acetylenic esters.…”
mentioning
confidence: 98%